Recombination breeding of Hevea brasiliensis in India: Clones evolved from the 1983 hybridization programme - John A; Mydin K.K; Nazeer M.A (Rubber Science, 2018)
Hundred and ten hybrid clones evolved from the 1983 hybridization programme and five ortets which were selections fromGG1 polyclonal seedlings planted at the Central Experimental Station of Rubber Research Institute of India (RRII) were evaluated over five years of tapping in seven small scale trials laid out in the farms of Kerala Agricultural University, Vellanikkara campus, Thrissur. The performance of these clones with respect to rubber yield, timber yield, summer yield depression, girth at opening and girth increment rate at immaturity and under tapping in comparison to the high yielding check clone RRII 105 is presented. A total of 22 promising clones could be identified from this population. Of these, 11 clones exhibited high rubber yield of which nine were dual purpose latex-timber clones (83/24, 83/35, 83/29, 83/173, 2/372, 83/191, 83/17, 83/224 and 83/234). Four of the latex-timber clones were from the cross RRIM 600 x G1 1, two belonged to the cross GT 1 x RRII 105, two more ortets selected from GG1 polycross trees and one belong to the cross PB 5/51 x RRII 105. Based on the criterion of timber yield, 11 clones exhibited very good timber yield of >0.2m3 tree-1 at the age of 20 years (83/31, 83/8, 83/12, 83/60, 83/111, 83/117, 83/120, 2/185, 83/19, 83/11 and 83/37) of which two clones had rubber yield on par with RRII 105, eligible to be designated as timber-latex clones (83/37 and 83/11). Among the 115 clones evaluated, the recovery of high rubber yielders was 10 per cent and high timber yielders was 11 per cent.
Keywords: Hevea brasiliensis; Hybrid clones; Latex-timber clones; Ortets; Rubber yield